The larvae of the European Helicopsyche species (Trichoptera: Helicopsychidae) - Waringer, Johann; Malicky, Hans; Živić, Ivana; Vicentini, Heinrich (Zootaxa, 2017)
This synoptic paper gives descriptions of the hitherto unknown or poorly known larvae of Helicopsyche megalochari Malicky 1974 and H. revelieri McLachlan 1884 (Trichoptera: Helicopsychidae). We present information on the morphology of the larvae and illustrate the most important diagnostic features. This information is used for the construction of a comprehensive larval key to the five European species of family Helicopsychidae. In the context of this key, larvae can be easily diagnosed by setation patterns of the dorsal head capsule, submentum shape, and propleuron morphology. With respect to distribution, Helicopsyche megalochari has been reported from the Greek Islands of Andros, Euboea, Ikaria, and Naxos whereas H. revelieri is known from the islands of Capraia, Corsica, and Sardinia. In addition, ecological characteristics and distributions of the European species are briefly discussed.